Fundamentalisme dalam Islam: Fenomena, Penyebab dan Dampak - Harjana, Dwi; Amri, Muhammad; Abdullah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to examine the phenomenon of fundamentalism in Islam from historical, ideological, and contemporary social perspectives. Using a qualitative approach with a literature review method, the research identifies two main dimensions of Islamic fundamentalism: as an expression of piety that seeks to preserve the purity of religious teachings, and as a reactive ideology with the potential to incite violence. The emergence of fundamentalism is driven by multiple factors, including responses to modernity and secularization, identity crises, failures in religious education institutions, and socio-political disparities. The most critical impacts of this phenomenon are social instability, narrowing of scholarly discourse, and the radicalization of youth. This study is expected to contribute to academic discourse on contemporary Islam and serve as a reference in formulating religious moderation strategies in pluralistic societies.